Evolution of mouse chromosome 17 and the origin of inversions associated with t haplotypes. - Hammer, M F (1989)
Mouse t haplotypes are variant forms of chromosome 17 that exist at high frequencies in worldwide populations of several species of house mouse. They are known to differ from wild-type chromosomes with respect to two relative inversions referred to as proximal and distal. An untested assumption has been that these two inversions originated in the chromosomal lineage leading to present-day t haplotypes. To investigate the evolutionary origins of these inversions and the possibility of additional inversions, interspecific crosses were performed between Mus spretus or Mus abbotti and laboratory strains of Mus domesticus that carried wild-type and t haplotypes forms of chromosome 17. The results provide evidence for the existence of two additional nonoverlapping inversions--one between the proximal and distal inversions and one between the centromere and the proximal inversion. These four inversions span nearly the entire region of t haplotype recombination suppression. Considering the distribution of these inversions among the species studied as well as the organization of the D17Leh66 family of DNA elements, we infer that the proximal inversion occurred on the lineage leading to the common ancestor of M. domesticus and M. abbotti, and that the other three inversions occurred on the separate lineage leading to present-day t haplotypes. Alternative models for the evolution of t haplotypes are discussed in light of these findings.